Taxonomic revision of Apteropilo Lea, 1908 (Coleoptera: Cleridae) - Bartlett, Justin S. (Zootaxa, 2009)
The endemic Australian genus Apteropilo Lea is revised and Pylusopsis Elston syn. n. found to be synonymous with the former. Apteropilo is redefined herein to include two previously described species (A. pictipes Lea (= Pylusopsis peckorum Kolibáč syn. n.) and A. chrysocome (Elston) comb. n.), and four new species (A. raldae sp. n., A. humerofuscus sp. n., A. clarinotus sp. n. and A. volans sp. n.). Species are arranged into three species-groups. A dichotomous key to species is provided and the systematic position of Apteropilo within Cleridae briefly discussed.